Sistem Informasi Customer Relation Management pada ISP PP. Juragan Wifi Berbasis Web - Mustika Ningrum; Kresno Murti Prabowo; Sabar .; Yudiansyah Fauzi (LPPM STMIK IKMI Cirebon, 2023)
Juragan Wifi Indonesia, PT (JWI) exists as an IT solution company that specializes in providing solutions, system integration, network and data center consulting as well as an Internet Service Provider. Oriented to help build smart network infrastructure in the provision of subscription internet services. In terms of customer service, JWI still uses non-automated and non-integrated services, so service is slower than automated CRM. To be able to compete with other ISPs and attract customers who will subscribe or retain existing customers, CRM should be changed to be automated and integrated. Therefore it is necessary to create a system. CRM information on ISPs to improve business quality and provide customer satisfaction